2017
DOI: 10.1177/1742715017720306
|View full text |Cite
|
Sign up to set email alerts
|

Leader perceptions and motivation as outcomes of followership role orientation and behavior

Abstract: Followership research posits that followers differ in the way they define and enact the followership role, which can have varying effects in relation to how leaders experience their own roles and responsibilities. Drawing from the role orientation literature and newly emerging research on followership, our study examines the indirect effects of followers' co-production (co-producing leadership outcomes) and passive (deferring to leadership influence) role orientations on leaderrated outcomes of perceived follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(178 citation statements)
references
References 94 publications
(173 reference statements)
5
172
0
1
Order By: Relevance
“…Although proactive employees are known for deliberately working to influence, alter, or otherwise change their environment (Grant & Ashford, ; Parker, Williams, & Turner, ), little is known about how they influence their leaders. Relatedly, followership scholars have called for examination of how leaders view proactive followership, and specifically whether these perceptions affect leadership behaviours (Carsten et al ., ; Uhl‐Bien et al ., ). Drawing on followership theory and the empowering leadership literature, we substantiated our expectations that proactive personality can induce leader engagement in empowering behaviours through engendering affect‐based trust from leaders.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although proactive employees are known for deliberately working to influence, alter, or otherwise change their environment (Grant & Ashford, ; Parker, Williams, & Turner, ), little is known about how they influence their leaders. Relatedly, followership scholars have called for examination of how leaders view proactive followership, and specifically whether these perceptions affect leadership behaviours (Carsten et al ., ; Uhl‐Bien et al ., ). Drawing on followership theory and the empowering leadership literature, we substantiated our expectations that proactive personality can induce leader engagement in empowering behaviours through engendering affect‐based trust from leaders.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, leaders may believe that employees with a proactive personality will handle challenging situations more effectively than will those who are inherently less proactive, thereby enhancing leaders' ability to meet especially complex and demanding workplace expectations. In support of this notion, Carsten et al (2017) found that leaders believe that followers with a proactive orientation (e.g., those willing to accept challenging tasks), compared to those with a passive orientation, are more likely to help them achieve their work-related goals. Taken together, we expect that employees with a more proactive personality are likely to demonstrate their competence, preparedness, and dedication to work; key components of cognition-based trust (McAllister, 1995).…”
Section: Proactive Personality and Trustmentioning
confidence: 91%
See 2 more Smart Citations
“…While reflecting on these models and followership types, it is important to mention that despite over three decades of research into followership, the stigma of followers being passive, deferential, or playing a secondary role in organizations' achievements (Carsten, Uhl‐Bien, & Huang, 2018; Kelley, 1988) is still present. The follower stigma is further amplified for middle managers who occupy positions that call for them to be both leader to their formal subordinates and followers to their superordinate managers.…”
Section: Literature Reviewmentioning
confidence: 99%